CRYSTALLINE COMET DUST: LABORATORY EXPERIMENTS ON A SIMPLE SILICATE SYSTEM - Thompson S.P.; Tang C.C.; Fonti S.; Verrienti C.; Blanco A.; Orofino V. (My University, 2003)
Spectra for certain comets show the presence of crystalline silicate dust grains believed to have been incorporated during comet formation. While grain crystallization is widely assumed to result from the thermal annealing of precursor amorphous grains, the physical processes behind the silicate amorphous-to-crystalline transition are poorly understood. This makes it difficult to place constraints on the evolutionary histories of both grains and comets, and consequently, on the nebular conditions in which they formed. It has, therefore, become necessary to study this process in the laboratory using simulated grain materials. In this paper, we discuss recent results from laboratory investigations into a basic amorphous MgSiO3 silicate annealed in the region of 1000 K. Our object is not to model the behavior of dust grains per se, but to study the underlying process of crystallization and separate the physics of the material from the astrophysics of dust grains. In our experiments, we bring together spectroscopic measurements made in the infrared with the high resolution structural probing capabilities of synchrotron X-ray powder diffraction. The combined use of these complementary techniques provides insights into the crystallization process that would not be easily obtained if each was used in isolation. In particular, we focus on the extent to which the identification of certain spectral features attributed to crystalline phases extends to the physical structure of the grain material itself. Specifically, we have identified several key features in the way amorphous MgSiO3 behaves when annealed. Rather than crystallize directly to enstatite (MgSiO3) structures, in crystallographic terms, amorphous MgSiO3 can enter a mixed phase of crystalline forsterite (Mg2SiO4) and SiO2-rich amorphous silicate where structural evolution appears to stall. Spectroscopically, the evolution of the 10 µm band does not appear to correlate directly with structural evolution, and therefore, may be a poor indicator of the degree of crystallinity. Indeed, certain features in this band may not be indicators of crystal type. However, the 20 mum band is found to be a good indicator of crystal structure. We suggest that forsterite forms from the ordering of pre-existing regions rich in SiO4 and that this phase separation is aided by a dehydrogenation processes that results in the evolutionary stall. The implications of this work regarding future observations of comets are discussed.